Zr-MOFs for CF4/CH4, CH4/H2, and CH4/N2 separation: towards the goal of discovering stable and effective adsorbents. Issue 8 (25th June 2021) - Demir, Hakan; Keskin, Seda
Abstract : The best Zr-MOF adsorbents among more than 100 Zr-MOFs are computationally identified for CF4 /CH4, CH4 /H2, and CH4 /N2 separations using a multi-criteria approach. Abstract : Zirconium metal–organic frameworks (MOFs) can be promising adsorbents for various applications as they are highly stable in different chemical environments. In this work, a collection of Zr-MOFs comprised of more than 100 materials is screened for CF4 /CH4, CH4 /H2, and CH4 /N2 separations using atomistic-level simulations. The top three MOFs for the CF4 /CH4 separation are identified as PCN-700-BPDC-TPDC, LIFM-90, and BUT-67 exhibiting CF4 /CH4 adsorption selectivities of 4.8, 4.6, and 4.7, CF4 working capacities of 2.0, 2.0, and 2.1 mol kg −1, and regenerabilities of 85.1, 84.2, and 75.7%, respectively. For the CH4 /H2 separation, MOF-812, BUT-67, and BUT-66 are determined to be the top performing MOFs demonstrating CH4 /H2 selectivities of 61.6, 36.7, and 46.2, CH4 working capacities of 3.0, 4.1, and 3.4 mol kg −1, and CH4 regenerabilities of 70.7, 82.7, and 74.7%, respectively. Regarding the CH4 /N2 separation, BUT-67, Zr-AbBA, and PCN-702 achieving CH4 /N2 selectivities of 4.5, 3.4, and 3.8, CH4 working capacities of 3.6, 3.9, and 3.5 mol kg −1, and CH4 regenerabilities of 81.1, 84.0, and 84.5%, in successive order, show the best overall separation performances. To further elucidate the adsorption in top performing adsorbents, the adsorption sites in these materials are analyzed using radial distribution functions and adsorbate density profiles. Finally, the water affinities of Zr-MOFs are explored to comment on their practical use in real gas separation applications. Our findings may inspire future studies probing the adsorption/separation mechanisms and performances of Zr-MOFs for different gases.